2022
DOI: 10.2147/ndt.s372557
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Contrast-Enhanced Ultrasound Combined with Serum miR-124 Level in Acute Cerebral Infarction and Their Correlation with the Contrast Enhancement of Carotid Atherosclerotic Plaque

Abstract: To investigate the predictive value of contrast-enhanced ultrasound (CEUS) combined with serum miR-124 level in acute cerebral infarction (ACI) and their association with the contrast enhancement of carotid atherosclerotic plaque. Methods: Totally 60 patients diagnosed with ACI and 60 controls were included in the study. All the subjects had carotid atherosclerotic plaques, and all of them were examined by CEUS and were tested for serum miR-124 levels. Results: Time to peak (TTP) and mean transit time (MTT) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These shortcomings may be resolved by combining MRA with other inspection methods. Zhao et al 21 showed that ultrasonic examination can improve the diagnostic efficacy of acute CI with high sensitivity and specificity and can evaluate the stability of atherosclerotic plaque. Yin et al 22 demonstrated that CU can dynamically monitor atherosclerotic plaque, reflect changes in vascular wall, and determine the extent of lesions by measuring indexes such as EDV, PSV, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These shortcomings may be resolved by combining MRA with other inspection methods. Zhao et al 21 showed that ultrasonic examination can improve the diagnostic efficacy of acute CI with high sensitivity and specificity and can evaluate the stability of atherosclerotic plaque. Yin et al 22 demonstrated that CU can dynamically monitor atherosclerotic plaque, reflect changes in vascular wall, and determine the extent of lesions by measuring indexes such as EDV, PSV, etc.…”
Section: Discussionmentioning
confidence: 99%